(untitled) (REMUNOM, 2025)
Mediated learning is a teaching model in which a mediator acts between the student and the stimuli in the environment, helping in the interpretation and assimilation of knowledge. This method can be applied in several ways, one of which is through playful activities, such as educational games. This study presents the proposal for the development of a didactic game called "Master of Chemistry", which aims to serve as a complementary tool in the teaching and learning process of analytical chemistry in higher education courses, especially in introductory disciplines. In its creation, accessible and low-cost materials were used in order to make the application more feasible. The game consists of cards with multiple-choice questions, true or false questions, discursive questions, as well as cards, a board and markers for the participants. In this way, a board game was obtained that favors the retention of content in a light and interactive way, making the teaching of chemistry more dynamic and less monotonous for the students, who begin to play a more active role in the learning process.